Quantum-limited mass flow of liquid 3He: Жидкий гелий - Lambert, G.; Gervais, G.; Mullin, W.J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We consider theoretically the possibility of observing unusual quantum fluid behavior in liquid 3He and solutions of 3He in 4He systems confined to nano-channels. In the case of pure ballistic flow at very lowtemperature conductance will be quantized in units of 2m2/h. We show that these steps should be sensitive to increases in temperature. We also use a random scattering matrix simulation to study flow with diffusive wall scattering. Universal conductance fluctuations analogous to those seen in electron systems should thenbe observable. Finally we consider the possibility of the cross-over to a one-dimensional system at sufficiently low temperature where the system could form a Luttinger liquid.